2022
DOI: 10.1007/s00170-022-09562-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing parameters on the surface quality of wrought Ni-based superalloy by ultrasonic-assisted electrochemical grinding

Abstract: Ni-based GH625 superalloy has been widely employed in the aerospace industry due to its high strength, outstanding corrosion resistance and high temperature resistance. A novel hybrid processing method of ultrasonic-assisted electrochemical grinding (UAECG) can achieve the high-effective removal rate for difficult-to-process materials and thereby avoids the stray corrosion during the process. This study systematically investigated the electrochemical dissolution behaviors of GH625 alloy at low current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Figure 7 shows graphically the effects of applied voltage on MRR and surface roughness at the constant value of grinding wheel speed 1,500 rpm and machining time 60 s. The MRR increases with the applied voltage when the applied voltage increases from 9 to 17 V. According to Faraday’s law, the MRR is proportional to the current density. Because the applied voltage directly affects the current density of the machining area, the MRR increases with the increase of the applied voltage (Ma et al , 2022). It can be seen from Figure 7(a) that the MRR increased by 0.138 g/min when the applied voltage is increased from 9 to 17 V in the 15 Wt.% NaCl electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows graphically the effects of applied voltage on MRR and surface roughness at the constant value of grinding wheel speed 1,500 rpm and machining time 60 s. The MRR increases with the applied voltage when the applied voltage increases from 9 to 17 V. According to Faraday’s law, the MRR is proportional to the current density. Because the applied voltage directly affects the current density of the machining area, the MRR increases with the increase of the applied voltage (Ma et al , 2022). It can be seen from Figure 7(a) that the MRR increased by 0.138 g/min when the applied voltage is increased from 9 to 17 V in the 15 Wt.% NaCl electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the introduction of ultrasonic vibration in grinding is a new method to improve the grinding quality of di cult-to-machine materials such as titanium alloys, nickel-based high-temperature alloys, ceramics and other materials in the aerospace industry [18][19][20][21][22][23][24][25][26]. Studies have shown that ultrasonic vibration-assisted grinding (UVAG) can introduce high-frequency micro-amplitude vibration, change the relative motion trajectory between the abrasive grain and the workpiece, so that the relative percentage of abrasive grain rubbing, ploughing, cutting effect changes, which can effectively reduce the grinding force and the grinding temperature, and enhance the integrity of the surface of the workpiece [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic-assisted welding is one of the important applications of ultrasonic technology with a high frequency (15 kHz to 40 kHz) and a low amplitude [2]. Different kinds of ultrasonic vibration-assisted machining processes, such as milling [3,4], turning [5,6], grinding [7,8], drilling [9,10], deburring [11,12], diamond machining (cutting) [13,14], electrical discharge machining (EDM) [15,16], abrasive water jet machining [17], hybrid laser-and ultrasonic-assisted machining [18,19], and surface finishing [20][21][22], etc., have been developed in recent years. The materials processed by the ultrasonic-assisted machining processes [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], in general, can be classified as brittle materials, hard-machining metallic materials, composite materials, and non-metallic materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The damage characteristics of ultrasonic vibration-assisted grinding of a C/SIC composite material has been studied in [7]. The effects of processing parameters on the surface quality of wrought Ni-based superalloy by ultrasonic-assisted electrochemical grinding has been investigated in [8]. The chip generation mechanism of Inconel 718 with ultrasonic-assisted drilling by step drill has been studied in [9].…”
Section: Introductionmentioning
confidence: 99%